Pd-Catalyzed C–H Silylation Reactions with Disilanes - Zhou, Bo; Lu, Ailan; Zhang, Yanghui (Synlett, 2019)
Pd-catalyzed C–H silylation reactions remain underdeveloped. General strategies usually rely on the use of complex bidentate directing groups. C,C-Palladacycles exhibit extremely high reactivity towards hexamethyldisilane and can be disilylated very efficiently. The C,C-palladacycles are prepared through halide-directed C–H activation. This account introduces Pd-catalyzed C–H silylation reactions with disilanes as the silyl source, and is focused on studies on the silylation of C,C-palladacycles.1 Introduction and Background2 Allylic C–H Silylation Reaction3 Coordinating-Ligand-Directed C–H Silylation Reaction4 Disilylation of C(sp2),C(sp2)-Palladacycles That are Generated by C(sp2)–H activation5 Disilylation of C(sp2),C(sp3)-Palladacycles That are Generated by C(sp3)–H Activation6 Disilylation of C,C-Palladacycles That are Generated through Domino Processes7 Summary and Outlook
Keywords: silylation; palladacycles; palladium; C–H activation; halides